Penjadwalan Cement Mill Berbasis Minimasi Faktor Klinker dalam Proses Pembilasan dan Impor Klinker - Nilda Tri Putri; Indah Kurnia Ramadhani (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
PT Semen Padang is one of the cement companies in Indonesia. Cement production influenced by the number of demand, raw materials and the number of the available machine. The number of demand increases with a corporate capacity which keeps the company had to set an optimal production schedule. Scheduling production should be followed by the availability of raw materials (clinker). The number of clinkers required influenced by the number of demands and clinker elapsed to the flushing process. Flushing process happens if the transition products produced from Non-OPC to a product OPC, for one flushing process causes clinker consumption 7% more than the existing capacity decreases. Deficient in a capacity covered by importing clinker which causes high-cost production. So, it necessary to make cement mill schedule by minimizing flushing process, so clinker that will be used become optimized. Steps that will be done in this study began with the survey system, identify problems, and data collection. Data collected are machine cement mill and kiln capacity, demands, and flushing process. Then designed a formulation model that minimizes clinker factor and the number of clinker imports needed, so that obtained scheduling machine cement mill to produce OPC and Non-OPC. Results obtained by reducing the number of flushing process because the cement mill designed to produce one type of product per day, so the flushing process could happen if there is transition cement production Non-OPC on the day-i to cement OPC on the day i+1. Cement OPC produced by Indarung II, III, and V. Indarung IV only produced cement Non-OPC, so the flushing process happened in Indarung II, III, and V.